Estudio de Algoritmos para la Distribución y Control de la Red de la Biblioteca perteneciente G.A.D. La Unión. - PARRA DÍAZ, KIMBERLY JOMARA (2018)
The technological advances, the science, are going to advance at a great step, therefore the wireless or wired networks in the same way, with more norms in their protocols, with adequate topologies designed exactly for each company or institution in which one is or wants undertake a job, in order to solve the problems that arise and to be able to take due control of the networks in each department that includes a company or institution. Algorithms today help solve everyday problems in everyday life, either through a manual of how to use an appliance, to the method that is usually used to solve mathematical operations. In this paper, a case study is presented, carried out in the Decentralized Autonomous Government of La Unión, directly related to the Library department with which this institution consists. Carrying out a brief analysis to the networks with which this department has, those in charge of the department as of G.A.D. Parish needs to have an exact network distribution between one department and another, so as not to have unnecessary expenses in structured network cabling, gutters, etc., and in this way be able to have a communication between one department and another, therefore an algorithm knowing that it will allow to realize a series of instructions that presents a model of solution to determine the type of problems or rules well defined and ordered to arrive at a solution.